2021
DOI: 10.18280/ijdne.160112
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Water Quality Using Canadian Water Quality Index: Green Belt Project/Kerbala-Iraq

Abstract: During the last five decades, a huge amount of water pollutants has been recorded in all water resources around the world. Therefore, the water quality has become an important indicator affecting the vitality and productivity of plants, which requires an effective technique to monitor all these pollutants. The main objective of this study is to assess the validity of groundwater for wells located within the boundaries of the Green Belt area in Karbala city/Iraq for irrigation of palm and olive trees. Whereas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…F1 and F2 can be calculated quickly, while F3 needs a few more steps [21]. Table 3 classifies and describes the water quality according to CWQI [22,23].…”
Section: Physical and Chemical Assessmentmentioning
confidence: 99%
“…F1 and F2 can be calculated quickly, while F3 needs a few more steps [21]. Table 3 classifies and describes the water quality according to CWQI [22,23].…”
Section: Physical and Chemical Assessmentmentioning
confidence: 99%
“…Compared with the single-factor evaluation, the comprehensive pollution index method used more comprehensive water quality indicators to assess water quality. The Canadian Water Quality Index is generally used to analyze the water quality of drinking water sources, which was obtained through the analysis of a long series of data [39,40]. The Nemeiro Pollution Index method used the actual measured concentration and standard concentration of selected indicators, and relates with the standard value of Class III water as the benchmark [41].…”
Section: Spatial Autocorrelation Analysis Of Water Quality Indexmentioning
confidence: 99%
“…The study also discussed and identified the most commonly used parameters. In their study, Al-Mohammed et al [4] utilized the CWQI index and came to the conclusion that in order to confirm good irrigation management, it is necessary to monitor future changes in groundwater in the study area, as well the characteristics that affect water quality.…”
Section: Introductionmentioning
confidence: 99%